2001
DOI: 10.1074/jbc.m100825200
|View full text |Cite
|
Sign up to set email alerts
|

The Conformation of the Glucocorticoid Receptor AF1/tau1 Domain Induced by Osmolyte Binds Co-regulatory Proteins

Abstract: The activation domains of many transcription factors appear to exist naturally in an unfolded or only partially folded state. This seems to be the case for AF1/tau1, the major transactivation domain of the human glucocorticoid receptor. We show here that in buffers containing the natural osmolyte trimethylamine N-oxide (TMAO), recombinant AF1 folds into more a compact structure, as evidenced by altered fluorescence emission, circular dichroism spectra, and ultracentrifugal analysis. This conformational transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
142
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(152 citation statements)
references
References 40 publications
10
142
0
Order By: Relevance
“…We recently demonstrated that the recombinant GR AF1 adopts a native-like folded conformation when incubated in the presence of the naturally occurring osmolyte, trimethylamine N-oxide, and in this folded conformation it strongly interacts with certain specific coregulatory proteins. These include the TATA box binding protein (TBP), the CREB binding protein, and steroid receptor coactivator 1 (22). Taken together, the data strongly suggest that proper folding of AF1 is an important requirement for its actions in regulating transcription.…”
mentioning
confidence: 62%
See 3 more Smart Citations
“…We recently demonstrated that the recombinant GR AF1 adopts a native-like folded conformation when incubated in the presence of the naturally occurring osmolyte, trimethylamine N-oxide, and in this folded conformation it strongly interacts with certain specific coregulatory proteins. These include the TATA box binding protein (TBP), the CREB binding protein, and steroid receptor coactivator 1 (22). Taken together, the data strongly suggest that proper folding of AF1 is an important requirement for its actions in regulating transcription.…”
mentioning
confidence: 62%
“…When expressed independently, the GR AF1 shows little structure and seems to exist as an ensemble of largely unstructured conformers (17, 18). The GR AF1 is known to interact with other transcription factors, and conditional folding has been suggested to be the key for these interactions (19)(20)(21)(22).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4. Because of their flexible structures, intrinsically disordered regions/domains of many signaling proteins including AR NTD/AF1 are capable of creating favorable surfaces for their efficient interactions with their target proteins (39) and can also be induced to fold spontaneously to native, functional forms by addition of certain osmolytes to the solvent (40,41). In this osmolyte-induced conformation, NTD/AF1 of the AR binds strongly to SRC-1 (41).…”
Section: Naturally Occurring Osmolytes: a Potential Therapeutic Tool mentioning
confidence: 99%